1996
DOI: 10.1111/j.1476-5381.1996.tb15739.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by P1075 and pinacidil of a calcium‐independent chloride conductance in conditionally‐immortal renal glomerular mesangial cells

Abstract: 1 Depolarization of mesangial cells has been shown to occur following an outward movement of chloride ions from the cell. We have shown previously that mesangial cells from the H-2K'-tsA58 transgenic mouse possess a significant whole-cell chloride conductance and consequently are a suitable preparation for the study of potential chloride channel inhibitors. 2 The effects on the whole-cell chloride conductance of the chloride channel inhibitor, 5-nitro-2-(3-phenylpropylamino)-benzoate (NPPB) and the potassium c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Alternatively, the volume sensitivity of the Ca 2+ -activated conductance described previously may represent a species-specific difference or a mixed contribution of Ca 2+ -activated and -independent Cl -channels to the whole-cell current. The nature of the Ca 2+ -independent Cl -current in mesangial cells has been less clear, but it is inhibited by 5-nitro-2-(3-phenylpropylamino)-benzoate (NPPB) and the K + channel openers pinacidil and P1075 [31]. The volume sensitivity of the current in previous studies was not assessed; however, the NPPB-sensitive current is likely to be I Cl.vol , as NPPB inhibits I Cl.vol in renal epithelia [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the volume sensitivity of the Ca 2+ -activated conductance described previously may represent a species-specific difference or a mixed contribution of Ca 2+ -activated and -independent Cl -channels to the whole-cell current. The nature of the Ca 2+ -independent Cl -current in mesangial cells has been less clear, but it is inhibited by 5-nitro-2-(3-phenylpropylamino)-benzoate (NPPB) and the K + channel openers pinacidil and P1075 [31]. The volume sensitivity of the current in previous studies was not assessed; however, the NPPB-sensitive current is likely to be I Cl.vol , as NPPB inhibits I Cl.vol in renal epithelia [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The Immortomouse® harbors a stably incorporated conditionally expressed transgene (Jat et al, 1991; Noble et al, 1992; Barber and Henderson, 1996; Dennis and Caplan, 1996b; Kanda et al, 1996; Walther et al, 1996), which encodes a variant of the tumor antigen (T-Ag) from the simian virus 40 A (SV40). A missense mutation of T-Ag (TsA) renders this protein functional at 33°C but inactive at body temperature (TsA58).…”
Section: Introductionmentioning
confidence: 99%
“…The Immortomouse® has been a source for conditionally immortalized cells from the endothelium (Kanda et al, 1996), renal mesangial cells (Barber and Henderson, 1996), Sertoli cells (Walther et al, 1996) mesenchymal cells (Dennis and Caplan, 1996b), cochlear hair cells (Kachar et al, 1986), skeletal muscle (Morgan et al, 1994; Ehler et al, 1995), epithelial cells (Whitehead et al, 1993; Kershaw et al, 1994; Whitehead and Joseph, 1994; Paradis et al, 1995), glial cells (Groves et al, 1993), and osteoclasts (Chambers et al, 1993). These immortalized cells continue to replicate at 33°C in the presence of IFNγ and do not exhibit differentiated phenotypes (Holley and Lawlor, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that these effects of P1075 are indeed due the opening of K ATP channels; in addition, 3 H-P1075 binding in segments of rat aorta is inhibited with IC 50 ≈400 nM (Bray and Quast 1992). It has been reported that P1075 also inhibits swelling-activated Clchannels (Holevinski et al 1994;Barber and Henderson 1996); however, the latter effect is not sensitive to inhibition by glibenclamide (Holevinski et al 1994). The aorta, as a large conduit vessel, is not ideally suited to reflect the changes in vascular structure and reactivity important in the pathology of diabetes (Tomlinson et al 1992).…”
Section: Introductionmentioning
confidence: 99%